I Let You Go - Mackintosh, Clare (London Sphere, 2014)
At the scene of a tragic accident, life changes immediately for everyone involved. Finding it impossible to stay in Bristol, Jenna Gray moves to a remote cottage on the Welsh coast. She is desperate to escape the past, but is haunted by the accident, by the loss of her son, and by her own fears. DI Ray Stevens is determined to get to the bottom of this case. The investigation takes him away from his family and he finds himself growing closer to Kate Evans, a young and forthright detective on his team. But Jenna's past is about to catch up with her, with devastating consequences
Include Epilogue
Keywords: Children--Death